2021
DOI: 10.1016/j.ijscr.2021.106324
|View full text |Cite
|
Sign up to set email alerts
|

Rare glomus tumor formation following trauma to the first digit

Abstract: Introduction Glomus tumors are rare and few cases are reported in the literature. They typically occur in females on the digits of the hands. Case presentation We report a case of a 30 year-old woman who presented with a mass that developed on the distal tip of her right thumb after traumatic injury. Magnetic resonance imaging (MRI) was conducted and mass resection was performed. Histopathology confirmed that the mass was a glomus tumor. Clinical discussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Research has indicated that the trans‐ungual method of nail bed incision approach has a higher incidence of postoperative nail plate deformity and tumor recurrence compared to the latero‐ungual method. Therefore, the latero‐ungual method is recommended, particularly for bulky and diffuse tumors, when employing the nail bed incision approach 17 . Nam et al 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has indicated that the trans‐ungual method of nail bed incision approach has a higher incidence of postoperative nail plate deformity and tumor recurrence compared to the latero‐ungual method. Therefore, the latero‐ungual method is recommended, particularly for bulky and diffuse tumors, when employing the nail bed incision approach 17 . Nam et al 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the latero-ungual method is recommended, particularly for bulky and diffuse tumors, when employing the nail bed incision approach. 17 Nam et al 18 conducted a study involving 32 cases of subungual GTs treated with nail bed incision surgery using horizontal and longitudinal incisions. During the follow-up, longitudinally oriented grooves/streaks, cracks, and tumor recurrence were observed in some cases.…”
Section: F I G U R Ementioning
confidence: 99%
“…Preliminary research has indicated that genetic modifications involve BRAF, NOTCH, PDGFRB, KRAS, and SMARCB1 [ 18 , 35 , 36 , 37 , 38 ]. Moreover, certain authors propose a traumatic etiology, drawing from a documented case involving a digital glomangioma [ 39 ]. Glomus tumors tend to affect individuals between 20 to 40 years old with female preponderance [ 23 , 40 ].…”
Section: General Information and Histopathological Considerationsmentioning
confidence: 99%